Compound heterozygosity of a De novo 16q24.1 deletion and missense mutation in COX4I1 leads to developmental regression, intellectual disability, and seizures - Zhen Liu; Mei He; Xuan Luo; Hu Pan; Xiao Mao; Jinping Su (Epilepsia Open)
Abstract The COX4I1 is responsible for encoding a crucial component of cytochrome c oxidase, integral to electron transport in the mitochondrial respiratory chain. Mutations in COX4I1 can result in a rare autosomal recessive disorder characterized by growth retardation, slow weight gain, microcephaly, and potentially, hematologic symptoms such as Fanconi anemia or neurological impairments including developmental regression and severe epilepsy. In this study, we report the first case of COX4I1 deficiency in China, identified in a 6‐year‐old boy. The patient exhibited developmental regression, epilepsy, low body weight, microcephaly, generalized muscle hypotonia, and progressive cerebral atrophy, but without hematologic damage or short stature. Compound heterozygosity for a de novo 16q24.1 deletion and a P152T missense mutation in the COX4I1 was detected. The P152T missense mutation is previously reported in patients with similar clinical manifestations. Additionally, we provide the first instance of progressive brain atrophy observed through MRI in a COX4I1 deficiency patient, broadening our understanding of the mutation spectrum and clinical phenotype of this genetic disorder. Plain Language Summary We discovered the first case of COX4I1 deficiency in China, identified in a 6‐year‐old boy. The patient exhibited developmental regression, epilepsy, low body weight, microcephaly, generalized muscle hypotonia, and progressive cerebral atrophy, but without hematologic damage or short stature. Compound heterozygosity for a de novo 16q24.1 deletion and a P152T missense mutation in the COX4I1 was detected. Additionally, we provide the first instance of progressive brain atrophy observed through MRI in a COX4I1 deficiency patient, broadening our understanding of the mutation spectrum and clinical phenotype of this genetic disorder.